Trading on Time - Djankov, Simeon; Freund, Caroline; Pham, Cong S. (2012)
We determine how time delays affect trade, using newly collected data on the days it takes to move standard cargo from the factory gate to the ship in 98 countries. We estimate a difference gravity equation and find that each additional day that a product is delayed prior to being shipped reduces trade by more than 1%. Put differently, each day is equivalent to a country distancing itself from its trade partners by about 70 km on average. We also find that delays have a relatively greater impact on exports of time-sensitive goods, such as perishable agricultural products.